2009
DOI: 10.1071/as08076
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzling Frequencies of CEMP and NEMP Stars

Abstract: Abstract:We present the results of binary population simulations of carbon-and nitrogen-enhanced metalpoor (CEMP and NEMP) stars. We show that the observed paucity of very nitrogen-rich stars puts strong constraints on possible modifications of the initial mass function at low metallicity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…From the difference between C and N, it is possible to distinguish the contribution from low‐ and intermediate‐mass AGB stars as the enrichment source of the observed metal‐poor stars. Pols et al (2009) showed that the IMF with the Gaussian distribution peaked at ∼10 M ⊙ (Komiya et al 2007) is rejected when trying to match the fraction between C‐rich and N‐rich stars, based on binary population synthesis models (see also Izzard et al 2009). Fluorine: F is one of the most interesting elements, although F abundances are estimated from only one infrared line from stellar spectra.…”
Section: Resultsmentioning
confidence: 99%
“…From the difference between C and N, it is possible to distinguish the contribution from low‐ and intermediate‐mass AGB stars as the enrichment source of the observed metal‐poor stars. Pols et al (2009) showed that the IMF with the Gaussian distribution peaked at ∼10 M ⊙ (Komiya et al 2007) is rejected when trying to match the fraction between C‐rich and N‐rich stars, based on binary population synthesis models (see also Izzard et al 2009). Fluorine: F is one of the most interesting elements, although F abundances are estimated from only one infrared line from stellar spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Others argued that the observed paucity of very N-rich stars puts strong constraints on the IMF at low metallicity (e.g. Komiya et al 2007) or may require a much more efficient dredge-up of carbon in low-mass, low-metallicity AGB stars than shown by detailed evolution models available to date (see Pols et al 2009;Izzard et al 2009 for a discussion). We argue that dQNe model is a promising explanation for both the ubiquity of CEMP-s stars and the near-absence of NEMP stars without the need for a revision of dredge-up models of AGB stars.…”
Section: Trends In Nitrogenmentioning
confidence: 99%
“…In addition to carbon enhancement, rare CEMP stars exhibit nitrogen overabundances, typically with [N/Fe] > 1.0 and [N/C] > 0.5, although this phenomenon depends on metallicity, it appears to be more frequent at [Fe/H] < 2.8 (∼ factor of 10) (Bessell & Norris 1982;Johnson et al 2007;Pols et al 2009Pols et al , 2012Roederer et al 2014a). The existence of a population of nitrogenenhanced metal-poor (NEMP) stars was predicted from the same evolution scenario, since AGB stars efficiently cycle carbon into nitrogen in their envelopes.…”
Section: Introductionmentioning
confidence: 99%